THE THEORITICAL FEASIBILITY OF BIOLOGY WORKSHEET ORIENTED BY ACTIVE LEARNING WITH MIND MAPPING STRATEGIES - FAJRI KUSUMA NINGRUM (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
The development of Biology worksheet oriented by active learning with Mind Mapping strategies on the material structure and function of plant tissues in class XI SMA objectives describe the feasibility of theoretical and empirical the Biology worksheet were oriented by Active Learning with Mind mapping strategies in the subject matter on the structure and function of tissues plants from the aspects of the presentation by structure, content and language. This type of research is the development of research. The result showed that developed biology worksheet was very good category with validation value from LKS 1, LKS 2, LKS 3, LKS 4 was 91.4%, 92.4%, 95.6%, 95.6% Keywords: Active Learning, Mind Mapping strategy, structure and function of the tissues of plants